The use of public spaces: the case of requalification of São Francisco street and the construction of the Cyclist’s Pocket Square, Curitiba, PR, Brazil (Terr@ Plural, 2021)
This article problematizes the process of requalification of São Francisco street and the construction of the Cyclist's Pocket Square, analyzing the transformation of the use of these public spaces after the intervention. Through participant analysis, with the approach with the subjects that use the spaces of the street and the square, the result points to the public space as fundamental in the discussion about citizenship. However, the appropriation of these spaces does not fail to generate conflicts among multiple actors with divergent interests. Despite the elaboration and execution of the project with a team of experienced professionals, the different forms of occupation of the street were not considered in the planning, which does not necessarily indicate a mistake in the requalification process. It happens that the subjects that appropriate and occupy these spaces are also transforming agents that create new uses and new perspectives according to their demands.
Keywords: Space; Public space; Democracy; Citizenship